Audiovisual collection management deselection and preservation of audiovisual collections of selected private and religious school learning resource centers in Marikina City - Sala, Virgilio F.; Cabbab, Johann Frederick A.; Peralejo, Elizabeth R. (Quezon City Institute of Library and Information Science, University of the Philippines Diliman, 2002)
This research study investigated the status of deselection and preservation practices adopted for audiovisual collections if private and religious school learning Resource Centers in Marikina City. The study used the descriptive survey method of research. Structured questionnaire were used in data gathering. It was also designed to 1) find out if private and religious school Learning Resource Centers in Marikina City practice deselection and preservation of audiovisual collections; 2) to know if these centers have written policies with regard the deselection and preservation of audiovisual collections; 3) to determine the reasons for deselection and preservation of audiovisual materials; 4) to know the methods and criteria used in the deselection and preservations; 5) to identify the problems encountered by the school librarians in the deselection and preservation process; 6) to present and suggest some improvements necessary to overcome the problems in the deselection and preservation of audiovisual collections. Seventeen (17) school Learning Resource Centers in Marikina City were surveyed and these were the Learning Resource Center of Charis School; Gentle Angel Learning Center; Holy Trinity of St. Therese of the Child Jesus; Infant Jesus Academy; Kostka School; Maranatha Christian Academy; Marikina Catholic School; Marikina Christian Academy; Marist School; Mother of Divine Providence; Nativity of Our Lady Parochial School; Our Lady of Perpetual Succor School; Regent Christian Academy; Roosevelt College; St. Nicholas School; St. Scholastica's Academy and Victorial School Foundation.
The findings of the study show that majority of the school Learning Resource Center (64.7) are managed by private corporations while the remaining (35.3) are managed by religious congregations. Roosevelt College High School Learning Resource Center has the biggest population among the group while Kostka School of Marikina Learning Resource Center has the smallest population. Majority of the Learning Resource Center (64.7) are headed by "Librarian". Eight (47.06) schools have only one staff handling the Learning Resource Center while four (23.53) school Learning Resource Centers have four staff members. Majority of these centers surveyed have "professional staff members" (82.35) while the rest (17.65) have "non-professional staff". Moreover, most (82.35) of the Learning Resource Centers have full time staff. All the seventeen Learning Resource Centers collected sound recordings, two-dimensional materials, electronic resources, video and other projected materials. Two-dimensional materials collected include flat pictures, photographs, charts, maps, and globes. The most common type of sound recordings collected by the Learning Resource Centers are cassette tapes and audio compact discs. The type of electronic resources, video and other projected materials collected by the Learning Resource Centers are video recordings, slides, video compact discs (VCD), CD-ROMs, transparencies, filmstrips and laser discs. Faculty, staff and students of the schools are the users of the Learning Resource Centers.
In the deselection practice, 16 or 92.75 of the Learning Resource Centers surveyed do not practice deselection of audiovisual materials while there is only 1 or 6.25 which practices deselection. All of the Learning Resource Centers surveyed practice preservation of audiovisual collections by applying preservation methods and techniques that are enumerated in the questionnaires. There is only one Learning Resource Center that has written policies with regard to the deselection of audiovisual collections. St. Scholastica's School of Marikina practices deselection of audiovisual collections for the following reasons: to save space and to make room for new materials, to have easy access to collection, to get rid of unused and out-of-date materials and improve the collection's, over-all appearance. In deselection, methods used are subjective weeding, mathematical approaches and combine criteria. The following criteria are followed in St. Scholastica's Academy School Learning Resource Centers in the deselection process; poor content, no available machine for the materials, dilapidated appearance, superseded editions, format of the materials are no longer in use, obsolete information content, duplicate copies, not circulating for a long time. Common problems encountered in the preservation process of audiovisual materials include budget, lack of knowledge about preservation of audiovisual collections, absence of trained personnel, inadequate facilities, absence of policies and guidelines for preservation work, and conflict between access and preservation.
The following are the conservation and preservation techniques employed at the school Learning Resource Centers; regular cleaning of the surroundings, repair, dubbing, provision of suitable storage, protection from living organisms, temperature and humidity control. After a through consideration of the findings of the study, the researcher concluded that deselection of audiovisual materials is not practiced in selected school Learning Resource Centers in Marikina City, primarily because most of these centers have limited numbers of audiovisual collection. And if deselection of audiovisual materials would be applied, a particular Learning Resource Center might end up to have smaller collection of audiovisual materials. Since Av materials are expensive, librarian-in-charge of process would be hesitant and would think of the possibility of retaining the materials. In addition, the school must allocate budget to be used in the preservation of audiovisual materials. Policies are useless without the 3 Ms (machine, money and manpower). Deselection should only be practiced when the Learning Resource Centers concerned have unlimited numbers of audiovisual collections.
It is recommended that future research be done to see how other factors affect the practice of deselection and preservation of audiovisual materials in school Learning Resource Centers as well as in Academic Libraries. Likewise, this study may be conducted on other Learning Resource Centers outside Marikina City or in other parts of the country which have Learning Resource Centers or collection of audiovisual materials. Most importantly, a similar study must be conducted after five or eight years to determine if new trends have emerged with regard the deselection and preservation of audiovisual collections. Institutions concerned must formulate standard policies with regard to the deselection and preservation of audiovisual materials in Learning Resource Centers. They should organize talks/lectures/workshops on current trends and future developments on the said topics. Authorities or experts on these topics may be invited to give all librarians in-charge of the audiovisual collection the opportunity to really know and understand them.
Vita.
Special Problem (Master of Library and Information Science)
Keywords: Audiovisual materials -- Conservation and restoration -- Philippines -- Marikina City; School libraries -- Collection development -- Philippines -- Marikina City; Selection of nonbook materials -- Philippines -- Marikina City